Malaysians' perspectives on solid waste management and e-Waze as an online waste reporting system - Mohamad Saad, Mohamad Zaki; Kamarudin, Shafinah; Meddin, Nur Ashikin; Maikol, Nathaniel; Ramaiya, Shiamala Devi; Leong, Wan Teng; Ramlan, Nur Hafizatun (Academica Press Solutions, 2023)
Due to Malaysia's population growth, solid waste production has grown, with each individual producing 1.17 kg of rubbish daily and Malaysia producing an estimated 39,000 tons of garbage daily. The trash produced by households, industry, and trade increases in volume and becomes a key problem if not properly managed. Municipalities or governments must spend more on waste management if it is inefficient need. Nowadays, individuals rely more on their phones for daily chores. A strategy of using mobile apps known as e-Waze is proposed to support the existing waste management system. e-Waze’s primary goal is to enable the public to direct lodging complaints with local authorities regarding waste complaints. To propose a new strategy for enhancing the waste management system to the public, it is necessary to investigate the public's acceptance of the proposed strategy. Therefore, a set of questionnaires has been prepared and delivered to Malaysian via WhatsApp to obtain their opinion on the solid waste management system and their willingness to report improper waste management through the online system. The questionnaire was designed structured style, with both closed and open-ended questions. This survey was conducted using a convenient sampling approach from February 25 until March 19, 2022. As a result, 100 respondents expressed dissatisfaction with their residential area's cleanliness. The respondents reported odours, rats, insects, and rubbish scattered around certain areas. In addition, 277 respondents agreed to use online platforms such as the e-Waze apps to report their waste complaints. Overall, using online technologies such as the e-Waze apps has the potential to be adopted by the public in facilitating the community to sustain the environment effectively.